FAT COMPOSITION CHANGES IN BONE MARROW DURING CHEMOTHERAPY AND RADIOTHERAPY - Carmona, Ruben (2014)
PURPOSE/OBJECTIVES(S): To quantify changes in bone marrow fat fraction and determine associations with peripheral blood cell counts. METHODS AND MATERIALS: In this prospective study, 19 patients received either highly myelotoxic (radiotherapy plus cisplatin, 5FU/MMC or cisplatin/5FU/cetuximab) or less myelotoxic treatment (capacitabine-radiotherapy or no concurrent chemotherapy). Patients underwent MR imaging and venipuncture at baseline, mid-treatment, and post-treatment visits. We performed mixed effects modeling of the mean proton density fat fraction (PDFF(%)) by linear-time, treatment, and vertebral column region (L4-S2 vs. T10-L3 vs. C3-T9), while controlling for cumulative mean dose and other confounders. Spearman rank correlations were performed by blood cell counts versus the difference in PDFF(%) pre- and post-treatment. RESULTS: Cumulative mean dose was associated with a 0.43% per Gy (p=.004) increase in PDFF(%). In the highly myelotoxic group, we observed significant changes in PDFF(%) per visit within L4-S2 (10.1%,p<.001) and within T10-L3 (3.93%,p=.01), relative to the reference C3-T9. In the less myelotoxic group, we did not observe significant changes in PDFF(%) per visit according to region. Within L4-S2, we observed a significant difference between treatment groups in the change in PDFF(%) per visit (5.36%,p=.04). Rank correlations of the inverse log difference in WBC versus the difference in PDFF(%) overall and within T10-S2 ranged from 0.69-0.78 (p<0.05). Rank correlations of the inverse log difference in ANC versus the difference in PDFF(%) overall and within L4-S2 ranged from 0.79-0.81 (p<0.05). CONCLUSION: MRI fat quantification is sensitive to marrow composition changes that result from (chemo)radiotherapy. These changes are associated with peripheral blood cell counts. This study supports a rationale for bone marrow sparing treatment planning to reduce the risk of hematologic toxicity.